Rainfall erosivity via mathematical modeling in a dry tropical region in the state of Alagoas - Costa, Julio César Calixto; Melo, Raví Emanoel de; Santos, Cícero Gomes dos (Revista Geama, 2025)
Water erosion is one of the main soil degradation processes caused by the impact of raindrops, resulting in the disintegration of particles and the transport and deposition of sediments. This study aims to determine the erosivity of rainfall (R factor) in the municipality of Minador do Negrão, Alagoas, via mathematical models and rainfall data from a 27-year historical series (1963-1989). The data were obtained from the Hidroweb portal and tabulated for regression analysis. Six mathematical models, including models proposed by different authors, were used to calculate the R factor. The results revealed an annual average rainfall of 646.76 mm, with the months from April to July having the highest rainfall rates, accounting for 60.93% of the annual rainfall. The analysis of the R factor allowed the classification of erosivity into different classes, ranging from weak to moderate, which is essential for soil conservation management. This factor was greater in the months with the highest rainfall. The correlation was high for all the mathematical models analyzed. Thus, the months from April--July were the most critical for the R factor. The mathematical modeling of this research can be used to determine the R factor in the municipality studied. Thus, this study contributes to the knowledge about the R factor in regions with scarce rainfall data, providing valuable information for the implementation of soil conservation practices during critical periods and assisting in the planning of sustainable management strategies.